IDDF2018-ABS-0221 Maintenance with faecal microbiota transplantation enhances deep remission in patients with ulcerative colitis in clinical remission. (June 2018) - Midha, Vandana; Singh, Arshdeep; Mahajan, Ramit; Mehta, Varun; Khattar, Husanpreet; Narang, Vikram; Sood, Ajit
Abstract : Background: Faecal microbiota transplantation (FMT) is beneficial in patients with active ulcerative colitis (UC), but its role in the maintenance of clinical remission and mucosal healing has not been assessed. Methods: This was a prospective, double-blind, randomised placebo-controlled trial conducted at Dayanand Medical College and Hospital, India. Twenty-eight patients with UC in clinical remission (Mayo Score=1) and histological remission (Nancy grade 0, 1) at 48 weeks. Results: Twenty-eight patients (50% males, aged 37.21±15.25 years) with UC in clinical remission were randomised to groups A and B. At the end of 48 weeks, none of the patients in either group suffered a clinical relapse (p=1). Deep remission was noted in significantly higher number of patients with FMT (n=12, 85.71%) when compared with placebo (n=4, 28.57%) (p=0.002). Histological remission was twice as high in patients treated with FMT (n=8, 57.14% vs placebo, n=4, 28.57%; p=0.13). Rate of endoscopic response was also higher with FMT (n=8, 57.14%) when compared to placebo (n=0, zero%) (p=0.001). No serious adverse events were noted. Conclusions: Maintenance with FMT can enhance achievement of deep remission and histological remission in patients with UC in clinical remission.